Розподілена обробка радіолокаційної інформації мережі оглядових систем спостереження - Старокожев, С. В.; Обод, І. І. (ХНУРЕ, 2023)
Information support of the airspace control and air traffic control system is carried out by primary and secondary radar systems. The presented work shows that the use of distributed processing of radar information in a synchronous network of primary and secondary radars, taking into account the possibility of using an equivalent factor for detecting and measuring the coordinates of an air object by two radars, is more appropriate than the existing structure of information support for an airspace control system.
Keywords: повітряний простор; об’єкт повітряний; система спостереження; інформація радіолокаційна; мережа синхронна